Cartographic Fictions : Maps, Race, and Identity - Piper, Karen Lynnea, 1965- (Book collections on Project MUSE., 2002)
Maps are stories as much about us as about the landscape. They reveal changing perceptions of the natural world, as well as conflicts over the acquisition of territories. This book looks at maps in relation to journals, correspondence, advertisements, and novels by authors such as Joseph Conrad and Michael Ondaatje. In her innovative study, the author follows the history of cartography through three stages: the establishment of the prime meridian, the development of aerial photography, and the emergence of satellite and computer mapping. (Midwest).